Planejamento de contratações de serviços: uma proposta de abordagem de gestão por meio do AHP em um Instituto Federal. - Silva, Giovanni D'Assunção (2023)
The institutions that make up the Federal Public Administration, in general, use a significant part of their budgetary resources with contracting services, which are executed by private companies under the indirect execution regime. Such contracts must be previously planned and, for this, it is imperative that the responsible servers observe the legal framework, which has as its main legal device the Normative Instruction No. 05/2017. The principle of legality links the actions of managers to the need for legislative compliance and such agents are faced with several factors that interfere in decision-making with regard to the planning of service contracts. Considering the above, the present work presents as main objective to propose a management approach that assists the various decision-making of managers of institutions and federal agencies responsible for planning the contracting of services. In support of this investigation, an examination of the legislation that governs the planning of service contracts was carried out, as well as a survey of the notes made by the literature on the interference variables. For the work unit, 22 campuses and the Rectory of the Federal Institute of Espírito Santo (IFES) were selected. With reference to the methods and procedures, a survey was used, and the questionnaire was used as a data collection technique. The valid sample consisted of 63 respondents, among the servers who were assigned to compose a team or committee for planning the contracting of services within the scope of the research unit. Additionally, the multicriteria Analytic Hierarchy Process (AHP) method was used to support the development of the management approach. Thus, through the AHP and based on the judgment of the stakeholders, it was possible to rank the main factors, subfactors and alternatives that impact on the planning of contracting services in order to assist managers in decision making Among the results, the factor "Adherence to standards" (NOR) showed a wide preference among stakeholders (66.4%), with emphasis on the subfactor "Existence of internal formal instruments" (EIF), which had 47% preference considering the general ranking of the subfactors. Regarding the alternatives, "Define work processes" (ALT 2) obtained 58.7% of the preference according to the judgment of the stakeholders. Another important aspect of the result refers to the creation of instruments that contribute to the achievement of efficiency in the process of contracting services. Associated with this is the training of the servers directly involved as an essential factor. The technical-technological product developed at the end of the work consists of a technical report with notes to assist managers of institutions and federal agencies in the decision-making inherent to the planning processes of contracting services governed by Normative Instruction nº 05/2017.